Study of counterion switch in rhodopsin using hybrid QM/MM simulations - พันธ์วงศ์, ชุตินธร (Progress in Applied Science and Technology, 2017)
Rhodopsin, a membrane protein on a retina, is responsible for visual perception in vertebrates. Rhodopsin contains retinal protonated Schiff base or RPSB (+1 charged) which undergoes isomerization from 11-cis to all-trans upon photo-excitation. The isomerization of RPSB induces changes in protein structure to complete the visual signaling. One of the important steps is a proton transfer from RPSB to its counterion (-1 charged). It is still not clear whether the 113th glutamic acid (E113) or E181 is a proton accepter from RPSB. However, many various studies have speculated a high possibility of counterion switch process from E113 (on a ground state) to E181 (on metarhodopsin I state). In this work, the detailed study of counterion switch is performed. The quantum mechanics/molecular mechanics (QM/MM) simulations are employed to obtained the free energy barriers for protonation of E113 and deprotonation of E181. It was found that protonation of E113 is more likely to occur than deprotonation of E181 due to different counterparts of their proton donor or acceptor.